The Effect of Silver Nanoparticles Manufacturd by Lactobacillus Bacteria on Some Bacterial Isolates Causing Gingivitis: Pengaruh Nanopartikel Perak yang Diproduksi oleh Bakteri Lactobacillus terhadap Beberapa Isolat Bakteri Penyebab Radang Gusi - Faris, Huda Natiq; Ghyadh, Bushra Ali; AL-Muswie, Rana Talib (Universitas Muhammadiyah Sidoarjo, 2024)
A Silver nanoparticles is considered to be able to kill multi resistant isolates due to its little dynamic effect on Microorganisms. The Gram-positive bacterium Lactobacillus bulgaricus was used in this investigation to manufacture NPs and evaluate their efficacy against certain pathogenic strains (Staphylococcus aureus, Staphylococcus mutans). For the production of nanoparticles, pure cultures of Lactobacillus bulgaricus were obtained from patients with gingivitis and dental caries and cultivated in